Global, regional, and national time trends in prevalence of metabolic dysfunction associated steatotic liver disease among women of reproductive age: an age-period-cohort analysis for the global Burden of Disease 2021 study - Jiehua Wei; Shanyu Lin; Senmao Zhang; Luying Fan; Lisa Jiang; Fan Xia; Ziye Li; Lizhang Chen; Zhiyong Zou; Tingting Wang (Annals of Medicine, 2025)
Objective This study aims to investigate the time trends in the prevalence of metabolic dysfunction associated steatotic liver disease (MASLD) among women of reproductive age (WRA) globally, regionally, and nationally from 1992 to 2021, and to explore associations with age, period, and birth cohort effects.Methods MASLD prevalence estimates were sourced from the Global Burden of Disease (GBD) 2021 study. We used an age-period-cohort model to analyze cohort and period effects, overall annual percentage changes (net drifts), annual percentage change in each age group, and longitudinal age-specific rates.Results The global prevalence of MASLD among WRA nearly doubled from 165 million in 1992 to 307 million in 2021. Fifty-one countries reported over one million cases, with China, India, and Indonesia leading. The global net drift of MASLD prevalence among WRA was 0.70% per year, with a range from 0.38% in the low sociodemographic index (SDI) region to 1.29% in the high-SDI region. Of 204 countries, 195 exhibited increasing age-standardized prevalence rates (net drift ≥ 0.0% per year), with Italy, Brunei Darussalam, and Oman showing the largest increases. Both period and cohort effects displayed unfavorable trends across most countries, except for Cambodia. Increased MASLD prevalence was associated with rising summary exposure values for high BMI, low physical activity, and high fasting plasma glucose.Conclusions MASLD in the WRA is an increasing health problem in all countries, and is accompanied by worsening period and cohort risks. These population-level trends warrant further investigation of their clinical implications for maternal health outcomes. Future research should focus on establishing evidence-based screening strategies and evaluating the clinical utility of interventions targeting liver health in WRA.